Pricing policy for development management - Meier, Gerald M. (Baltimore : Published for the Economic Development Institute of the World Bank [by] Johns Hopkins University Press, 1983)
This book discusses about the role of prices in a country's development process. It intends to provide a would-be project evaluator with an appreciation of the underlying logical structure of cost-benefit project appraisal.
Includes index.
Includes bibliographical references: p. 255-257
ne 21/01/2019
Loans
Keywords: Pricing; Price regulation; Economic development